Responsibility of Persons with Intellectual Disabilities in Criminal Acts in Case of Child Abuse (Study of Decision No. 47/PID.SUS/2018/PN. TRT) - Sirejeki Sirejeki; Joko Setyono (Budapest International Research and Critics University, 2022)
A person with a disability on average has difficulty in reasoning, processing, about something good and bad. This will certainly be a problem if he is caught in a criminal case. How the legal protection for perpetrators of persons with disabilities and what is is their criminal responsibility. This research was conducted by means of normative legal research. The research method used is a Case Approach and a comparative approach. The results of the study show that perpetrators with disabilities are given legal protection as stated in the legislation, namely the 1945 Constitution of the Republic of Indonesia, Law Number 19 of 2011 concerning Ratification (Convention Regarding the Rights of Persons with Disabilities) and Law Number 8 of 2016 concerning Persons with Disabilities. Accountability of perpetrators with intellectual disabilities in cases of child abuse. Case study Decision No. 47/Pid.Sus/2018/Pn. Trt the perspective of Islamic law according to the hadith of the Prophet SAW narrated by Imam Ahmad and Abu Daud: